Greenhouse gas emissions and global warming potential of traditional and diversified tropical rice rotation systems - Weller, Sebastian; Janz, Baldur; Jörg, Lena; Kraus, David; Racela, Heathcliff S. U.; Wassmann, Reiner; Butterbach-Bahl, Klaus; Kiese, Ralf (Wiley, 2016)
Global rice agriculture will be increasingly challenged by water scarcity, while at the same time changes in demand (e.g. changes in diets or increasing demand for biofuels) will feed back on agricultural practices. These factors are changing traditional cropping patterns from double-rice cropping to the introduction of upland crops in the dry season. For a comprehensive assessment of greenhouse gas (GHG) balances, we measured methane (CH4)/nitrous oxide (N2O) emissions and agronomic parameters over 2.5 years in double-rice cropping (R-R) and paddy rice rotations diversified with either maize (R-M) or aerobic rice (R-A) in upland cultivation. Introduction of upland crops in the dry season reduced irrigation water use and CH4 emissions by 66–81% and 95–99%, respectively. Moreover, for practices including upland crops, CH4 emissions in the subsequent wet season with paddy rice were reduced by 54–60%. Although annual N2O emissions increased two- to threefold in the diversified systems, the strong reduction in CH4 led to a significantly lower (P < 0.05) annual GWP (CH4 + N2O) as compared to the traditional double-rice cropping system. Measurements of soil organic carbon (SOC) contents before and 3 years after the introduction of upland crop rotations indicated a SOC loss for the R-M system, while for the other systems SOC stocks were unaffected. This trend for R-M systems needs to be followed as it has significant consequences not only for the GWP balance but also with regard to soil fertility. Economic assessment showed a similar gross profit span for R-M and R-R, while gross profits for R-A were reduced as a consequence of lower productivity. Nevertheless, regarding a future increase in water scarcity, it can be expected that mixed lowland–upland systems will expand in SE Asia as water requirements were cut by more than half in both rotation systems with upland crops.